Aberrant right subclavian artery: the association with chromosomal defects and the related post-natal outcomes in a third level referral centre. (17th February 2022) - Morlando, Maddalena; Morelli, Carmela; Del Gaizo, Fortuna; Fusco, Adelaide; De Fazio, Federica; Di Pietto, Laura; Moccia, Gianfranco; Spinelli Barrile, Ludovica; Schiattarella, Antonio; De Franciscis, Pasquale; Colacurci, Nicola; Russo, Maria Giovanna
Abstract: Aberrant right subclavian artery (ARSA) is the most common embryologic abnormality of the aortic arch. The presence of ARSA has been previously associated with an increased risk of Down syndrome. ARSA at birth may be associated with dysphagia, respiratory distress and stridor and there is no clear evidence‐based management. The aim of this study was to describe the associations with chromosomal abnormalities and the postnatal outcome of fetuses diagnosed with ARSA. We analysed fetuses diagnosed antenatally with ARSA between January 2013 and September 2019 in the fetal echocardiography unit of the Hospital Monaldi, University 'Vanvitelli' of Naples, Italy. The results showed fifty fetuses diagnosed with ARSA, all confirmed after birth. The ARSA was an isolated finding in 46 fetuses (92%), while in 4 fetuses the ARSA was associated with other cardiac and/or extra-cardiac anomalies. Only one fetus was diagnosed with trisomy 21 (2%). In this fetus the ARSA was the only ultrasound anomaly identified. There were no cases necessitating referral due to the presence of compression symptoms at birth. The presence of ARSA was associated with trisomy 21 in the 2% of cases in our series and there were no neonatal complications due to airway compression at birth. IMPACT STATEMENT: What is already known on this subject? Aberrant right subclavian artery (ARSA) is the most common embryologic abnormality of the aortich arch. ARSA at birth could be associated with dysphagia, respiratory distress and stridor and no evidence-based management of these fetuses has been described yet. The presence of ARSA has been previously associated with an increased risk of Down syndrome. What do the results of this study add? This study confirms known data on association with chromosomal defects and provides some original data on the absence of symptomatology due to tracheal compression with a postnatal follow-up up to three years of age. What are the implications of these findings for clinical practice and/or further research? Our findings suggest that in cases with adequate prenatal assessment performed by experienced clinicians, delivery can safely take place at local hospitals, with no need of referral soon after birth. The use of transthoracic echocardiography to confirm the diagnoses of ARSA after birth and to plan the next follow-up appointments can be supported.